Balanced-Budget Fiscal Stimuli of Investment and Welfare Value - Cesare Dosi; Michele Moretto; Roberto Tamborini (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
Is a fiscal stimulus of investment a viable complement to, or substitute for, monetary policy? We address this issue by means of real option valuation of a private investment which generates private as well as public benefits. A surge in uncertainty about private profitability delays investment to an extent that may not be offset by monetary policy (conventional or not). Turning to fiscal policy, we examine the welfare effects of different policy schemes: (i) a simple subsidy on investment, (ii) a balanced-budget stimulus where the subsidy is covered by profit taxation, and (iii) by taxing public benefits as well. We show that, under a balanced-budget stimulus, investment acceleration may come at the expense of decreased total (private and public) welfare and that the higher is uncertainty about private returns, the more likely is a net efficiency loss. However, the risk of such negative outcome strongly declines when the government spending is balanced by taxing both private and public returns on investment.
Keywords: 330